The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.jpubeco.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Public child care and mothers' labor supply—Evidence from two quasi-experiments

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
147
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(172 citation statements)
references
References 22 publications
11
147
2
6
Order By: Relevance
“…Thus, policies that make it easier for women with young children to work, or policies that help reintroduce mothers of older children to high-return wage employment, could be an especially useful tool for boosting FLFP. Rigorous research in the United States (US), Europe, and Latin America has found varying, though often positive, impacts of childcare facilities on FLFP; see the literature review in Bauernschuster and Schlotter (2015). Bauernschuster and Schlotter (2015) argue that subsidized childcare will likely be effective in contexts where it does not simply crowd out informal caregiving arrangements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, policies that make it easier for women with young children to work, or policies that help reintroduce mothers of older children to high-return wage employment, could be an especially useful tool for boosting FLFP. Rigorous research in the United States (US), Europe, and Latin America has found varying, though often positive, impacts of childcare facilities on FLFP; see the literature review in Bauernschuster and Schlotter (2015). Bauernschuster and Schlotter (2015) argue that subsidized childcare will likely be effective in contexts where it does not simply crowd out informal caregiving arrangements.…”
mentioning
confidence: 99%
“…Rigorous research in the United States (US), Europe, and Latin America has found varying, though often positive, impacts of childcare facilities on FLFP; see the literature review in Bauernschuster and Schlotter (2015). Bauernschuster and Schlotter (2015) argue that subsidized childcare will likely be effective in contexts where it does not simply crowd out informal caregiving arrangements. In the Indonesian context, this suggests that urban women, who often have family in rural areas, could especially benefit from services.…”
mentioning
confidence: 99%
“…Many studies rely therefore on quasi-experimental approaches, mainly the difference-in-difference method, often exploiting an expansion of subsidized child care as a natural experiment (Havnes and Mogstad, 2011;Cascio, 2009;Bauernschuster and Schlotter, 2013;Givord and Marbot, 2013;Nollenberger and Rodriguez-Planas, 2011;Bettendorf et al, 2012;Lefebvre et al, 2009;Lundin et al, 2008;Fitzpatrick, 2010 timating employment responses, they exploit spatial and temporal variation on the municipality level. Their empirical analysis is conducted using administrative data that covers the entire Norwegian population over the relevant period.…”
Section: Child Care Policies and Maternal Employmentmentioning
confidence: 99%
“…German study exploits the introduction of the legal claim to a place in kindergarten for three-to six-year old children in 1996 in West Germany to estimate the effect on maternal employment (Bauernschuster and Schlotter, 2013). Results from two different quasi-experimental approaches consistently document large positive effects on employment among mothers whose youngest child is three to four years old.…”
Section: Child Care Policies and Maternal Employmentmentioning
confidence: 99%
“…Most of these studies have focused on the effects of childcare provision for preschool-aged children. Exploiting temporal and regional variation in childcare supply and estimating difference-in-differences models or relying on eligibility cut-offs in an instrumental variable or regression discontinuity setting, these studies provide mixed evidence (Gelbach 2002, Berlinski & Galiani 2007, Baker et al 2008, Cascio 2009, Fitzpatrick 2010, Havnes & Mogstad 2011, and Bauernschuster & Schlotter 2015. Childcare provision for school-aged children has attracted little attention, although primary school-aged children also require a significant amount of maternal care.…”
Section: Introductionmentioning
confidence: 99%